Parents’ satisfaction and children's acceptance of nasal compared to oral midazolam for sedation in two consecutive pediatric dental treatments: a randomized controlled study - Fux-Noy, Avia; Saadi, Qamar; Shmueli, Aviv; Halperson, Elinor; Ram, Diana; Moskovitz, Moti (Frontiers in Dental Medicine, 2023)
Introduction: Midazolam, by either the oral or the nasal route, is safe and effective in reducing anxiety and improving behavior in children during dental procedures. Aim: to compare both children's acceptance and parents' satisfaction with midazolam premedication, when administered as an oral syrup or as a nasal spray and explore whether there were positive or negative changes in acceptance during consecutive dental treatment visits. Methods: Randomized controlled study among uncooperative 2-6-year-old children who needed at least two similar dental treatments. On each visit, the acceptability of the medication was assessed as good, fair, or poor. The duration of crying after medication administration was recorded. Additionally, parents were asked to rank their satisfaction with the mode of administration. Results: The study group included 60 children; 30 patients received midazolam orally and 30 nasally. Route of administration did not correlate with medication acceptance in the first (p=0.11) and second visit (p=0.61). However, in the oral group, medication acceptance of 73% of children deteriorated on the second visit, compared to 33% in the nasal group (p=0.01). The difference was statistically significant also for crying (p=0.00), with more children in the oral group deteriorating and crying on the second visit. Parents of children in the oral group expressed less satisfaction with premedication administered on the second visit than did parents of children in the nasal group, p=0.00. Poor medication acceptance at the first visit (p=0.014) and oral route of administration (p=0.014) were found to be predictors of poor medication acceptance at the second visit. The probabilities of poor premedication acceptance in the second treatment were 9 times greater for the oral route compared to the nasal. Conclusions: Acceptance of premedication is expected to deteriorate after the first treatment visit, especially in the oral route of administration. Dentists should consider nasal spray administration for young pediatric patients who need more than one dental treatment. Parents should be prepared for possible resistance or refusal by children.The full trial protocol can be accessed at clinicaltrials.gov (registration number: NCT02679781, date of registration: 10/02/2016).